Analgesic Potential of Flavonoids for Cancer-Associated Pain and its Treatments: Systematic Review - Maycon Giovani Santana; Rachel Verdan Dib; Matheus Cavalcante de Deus; Ana Lúcia Teodoro; Denise Gonçalves (Revista Brasileira de Cancerologia)
Introduction: Pain is a prevalent and debilitating symptom in cancer patients, reducing quality of life. Its management is often challenging, with conventional pharmacological treatments associated with undesirable side effects. Natural compounds as flavonoids have garnered attention among emerging therapeutic approaches. Flavonoids are phenolic compounds abundant in the plant kingdom, recognized for their antitumor, anti-inflammatory, anti-allergic, and antiangiogenic properties. However, their analgesic potential is yet to be explored. Objective: Literature review of the analgesic potential of flavonoids in cancer pain and/or treatment-related. Method: A search was conducted at the PubMed, SciELO, Lilacs, and Cochrane Library databases with the keywords “cancer”, “flavonoids,” and “pain”. Inclusion criteria were clinical studies published between 2010 and 2024 in English, Portuguese, or Spanish, with patients over 18 years of age, that investigated the association among cancer, flavonoids, and pain. All the studies were submitted to risk of bias analysis. The study was approved by PROSPERO and based on PRISMA. Results: 14 clinical trials were included. The most frequently studied compound was Epigallocatechin gallate, for breast, lung, head and neck, and esophagus (n=9) cancers. All the studies investigated flavonoids in treatment-related pain, demonstrating pain reduction in cases of radiodermatitis, mucositis, esophagitis, and onycholysis. Flavonoid administration, either prophylactic or therapeutic, was well tolerated when applied topically or orally. Conclusion: Flavonoids exhibit promising analgesic potential in cancer-related pain, with minimal or no reported side effects. Further clinical studies are needed to elucidate their effectiveness in this context.